2002
DOI: 10.1046/j.1442-9993.2002.01176.x
|View full text |Cite
|
Sign up to set email alerts
|

Seedling establishment, mortality, tree growth rates and vigour of Acacia nilotica in different Astrebla grassland habitats: Implications for invasion

Abstract: A demographic study was conducted in the northern Australian Astrebla grasslands to determine the importance of habitat type in influencing invasion patterns of Acacia nilotica , an exotic leguminous tree from Africa and Asia. One of the repeated patterns observed for A. nilotica is that denser populations are often associated with riparian habitats. Data available on this species do not enable us to determine which of a number of processes has lead to the formation of this pattern. Several explanations were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Our field observations suggest that ramet production could be more common in relatively more disturbed conditions (e.g. with higher soil erosion levels); as other authors have suggested, root exposure and meristem activation, which increase in frequency with increasing soil erosion, may be responsible for active vegetative spread under these circumstances (Radford et al, 2002). This highlights the importance of addressing clonal propagation in semi-desert shrubs and trees in order to fully understand their population dynamics.…”
Section: Article In Pressmentioning
confidence: 64%
See 1 more Smart Citation
“…Our field observations suggest that ramet production could be more common in relatively more disturbed conditions (e.g. with higher soil erosion levels); as other authors have suggested, root exposure and meristem activation, which increase in frequency with increasing soil erosion, may be responsible for active vegetative spread under these circumstances (Radford et al, 2002). This highlights the importance of addressing clonal propagation in semi-desert shrubs and trees in order to fully understand their population dynamics.…”
Section: Article In Pressmentioning
confidence: 64%
“…In many desert trees seed germination is high in disturbed sites, apparently due to the stimulating effect of high temperatures under these conditions (Smith and Goodman, 1986;Bush and Van Auken, 1990;Teketay, 1998;Flores, 2001). Their ability to germinate and establish over a wide range of ecological conditions may confer these species a competitive advantage in the use of space and resources over other vegetation elements (Smith and Shackleton, 1988;Radford et al, 2002).…”
Section: Article In Pressmentioning
confidence: 99%
“…species that lack nectar, including A. nilotica (Stone et al. , 1998) – the most invasive African acacia in Australia (Radford et al. , 2002).…”
Section: Literature Review: Reproductive Biology Of Australian Acaciasmentioning
confidence: 99%
“…, 2000; Inderjit, 2005; Richardson & Pyšek, 2006) and in general, individual habitats differ in the number of alien species they contain (e.g. Crawley, 1987; Alvarez & Cushman, 2002; Byers, 2002; Radford et al. , 2002; García‐Robledo & Murcia, 2005; Sádlo et al.…”
Section: Introductionmentioning
confidence: 99%